2011
DOI: 10.1042/bj20110949
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of endolysosomal Ca2+ signalling in health and disease

Abstract: Endosomes, lysosomes and lysosome-related organelles are emerging as important Ca2+ storage cellular compartments with a central role in intracellular Ca2+ signalling. Endocytosis at the plasma membrane forms endosomal vesicles which mature to late endosomes and culminate in lysosomal biogenesis. During this process, acquisition of different ion channels and transporters progressively changes the endolysosomal luminal ionic environment (e.g. pH and Ca2+) to regulate enzyme activities, membrane fusion/fission a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
461
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(469 citation statements)
references
References 315 publications
(429 reference statements)
4
461
1
3
Order By: Relevance
“…Another attractive hypothesis for impaired endolysosomal trafficking is a defect in vesicle fusion or ARTICLE fission processes. It has been postulated before that Ca 2 þ is required for vesicular fusion processes and thereby regulates trafficking of vesicular cargo proteins 30,32,33 . In accordance with this hypothesis, we found that in WT MEFs chelation of cytosolic Ca 2 þ by 1,2-bis(2-aminophenoxy)ethane-N,N,N 0 ,N 0 -tetraacetic acid tetrakis(acetoxymethyl ester) (BAPTA-AM) mimics the effect on EGF trafficking observed in TPC2 À / À MEFs (Fig.…”
Section: Articlementioning
confidence: 99%
“…Another attractive hypothesis for impaired endolysosomal trafficking is a defect in vesicle fusion or ARTICLE fission processes. It has been postulated before that Ca 2 þ is required for vesicular fusion processes and thereby regulates trafficking of vesicular cargo proteins 30,32,33 . In accordance with this hypothesis, we found that in WT MEFs chelation of cytosolic Ca 2 þ by 1,2-bis(2-aminophenoxy)ethane-N,N,N 0 ,N 0 -tetraacetic acid tetrakis(acetoxymethyl ester) (BAPTA-AM) mimics the effect on EGF trafficking observed in TPC2 À / À MEFs (Fig.…”
Section: Articlementioning
confidence: 99%
“…Voltage-gated calcium channels (VGCCs) are found in excitable cells (e.g., glial cells, muscle, neurons, etc.) [3][4][5][6]. There are at least six classes of VGCCs (L-, N-, P/Q-, R-and the T-type channels) that are distributed according to cell type and location, and that may be distinguished by electrophysiological, pharmacological, and structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…There are many hypotheses about the mechanisms of NAADP action. Much evidence suggests that NAADP induces small yet localized cytoplasmic Ca 2+ -signals subsequently amplified into regenerative global Ca 2+ -signals by recruitment of endoplasmic reticulum via calcium-induced calcium release (CICR) [17]. The actual data collected on the NAADP-receptors remain disputable.…”
Section: Resultsmentioning
confidence: 99%
“…The actual data collected on the NAADP-receptors remain disputable. The potential NAADP-sensitive Ca 2+ -channels candidates include TRPML1, TRPM2, TPCs and even RyRs [16,17]. In order to investigate the effects of NAADP in the cell, there was synthesized the selective antagonist of NAADP -NED-19.…”
Section: Resultsmentioning
confidence: 99%